Night work and breast cancer – results from the German GENICA study - Pesch, Beate; Harth, Volker; Rabstein, Sylvia; Baisch, Christian; Schiffermann, Markus; Pallapies, Dirk; Bonberg, Nadine; Heinze, Evelyn; Spickenheuer, Anne; Justenhoven, Christina; Brauch, Hiltrud; Hamann, Ute; et al. (Scandinavian Journal of Work, Environment & Health, 2010)
' ' OBJECTIVES ': 'Some epidemiological and animal data indicate that night work might increase the risk for breast cancer. We have investigated the risk in a German population-based case–control study known as GENICA (gene environment interaction and breast cancer). ' ' METHODS ': 'The GENICA study involved interviews to assess shift work information in 857 breast cancer cases and 892 controls. We estimated risks of employment status and night shift characteristics using conditional logistic regression models, adjusting for potential confounders. Resampling and bootstrapping were applied to adjust the risk estimates for a potential selection bias. ' ' RESULTS ': 'Among 1749 women, 56 cases and 57 controls worked in night shifts for ≥1 year, usually in the healthcare sector (63.0% of controls). Female night workers were more frequently nulliparous and low-educated than day workers (28.6% versus 17.8% and 12.3% versus 9.2%, respectively). Fewer women in night work had ever used post-menopausal hormone therapy (35.7% versus 51.9%). An elevated breast cancer risk was not associated with having ever done shift or night work when compared to women employed in day work only [odds ratio (OR) 0.96, 95% confidence interval (95% CI) 0.67–1.38 and OR 0.91, 95% CI 0.55–1.49, respectively). Women who reported >807 night shifts, the third quartile of the distribution among controls, experienced a breast cancer risk of 1.73 (95% CI 0.71–4.22). Night work for ≥20 years was associated with an OR of 2.48 (95% CI 0.62–9.99) based on 12 cases and 5 controls. ' ' CONCLUSIONS ': 'Long-term night work was associated with a modestly, but not significantly, increased breast cancer risk, while having ever done night work was not. The precision of the results was limited by a low prevalence of night work in this study population.
Keywords: breast cancer; cancer; case–control study; GENICA study; Germany; health; night work; occupation; shift work